Decreased Movement Path Tortuosity Is Associated With Improved Functional Status in Patients With Traumatic Brain Injury. Issue 1 (January 2016) - Kearns, William D.; Scott, Steven; Fozard, James L.; Dillahunt-Aspillaga, Christina; Jasiewicz, Jan M.
Abstract : Objective: To determine if movement path tortuosity in everyday ambulation decreases in Veterans being treated in a residential setting for traumatic brain injury. Elevated path tortuosity is observed in assisted living facility residents with cognitive impairment and at risk for falls, and tortuosity may decrease over the course of cognitive rehabilitation received by the Veterans. If observed, decreased tortuosity may be linked to improved clinical outcomes. Design: Longitudinal observational study without random assignment. Setting: Veterans Affairs Medical Center inpatient residential polytrauma treatment facility. Patients: Twenty-two Veterans enrolled in a postacute predischarge residential polytrauma treatment facility. Interventions: None, observation-only. Main Outcome Measure: Mayo-Portland Adaptability Index-4, and movement path tortuosity measured by Fractal Dimension (Fractal D). Fractal D was obtained continuously from an indoor movement tracking system primarily used to provide machine-generated prompts and reminders to facilitate activities of daily living. Patients were deemed "responders" ( N = 10) if a significant linear decline in Fractal D occurred over the course of treatment, or nonresponders ( N = 12) if no significant decline was observed. Results: Responders had lower discharge Mayo-Portland Adaptability Inventory scores (mean = 32.6, SD = 9.53) than non-responders (mean = 39.5, SD = 6.02) ( F = 2.07, df = 20, P = .05). Responders and nonresponders did not differ on initial injury severity or other demographic measures. Conclusions: Fractal D, a relatively simple measure of movement path tortuosity can be linked to functional recovery from traumatic brain injury.